Perennial flower strips increase pollinator and natural enemy abundance but have limited effects on pest control in adjacent crops - Neus Rodríguez-Gasol; Maria Viketoft; Elodie Chapurlat; Johan A. Stenberg; Mattias Jonsson; Ola Lundin (Agriculture, Ecosystems & Environment, 2026)

Soil‐Borne Pathogens Reflect Agricultural Land‐Use Legacies - Tord Ranheim Sveen; Ida Junker Madsen; Eva Gustavsson; Sara Cousins; Franz Buegger; Karin Pritsch; Laura Riggi; Janne Bengtsson; Maria Viketoft; Mo Bahram (Ecology Letters, 2026)
Historical land‐use changes shape present‐day biodiversity through legacy effects, but the duration and mechanisms of these legacies are poorly understood. We used historical land‐use maps in two Swedish landscapes across three centuries to examine the persistent influence of historical land use on plant and soil microbial communities. Overall, bacteria showed stronger legacy effects than fungi, but effects varied across functional groups of plant‐associated and free‐living taxa. However, soil‐borne plant pathogenic fungi showed a persisting influence of arable land use which gradually disappeared after ~150 years, suggesting that land‐use legacies decay over time. This dilution could relate to changing plant communities but also to changes in microbial associations, as suggested by species co‐occurrence patterns over time. Our findings provide novel and crucial information on the duration of land‐use legacies and single out soil‐borne plant pathogens as key indicator groups of historical land use in present‐day ecosystems.

Soil moisture and fertility drive earthworm diversity in north temperate semi-natural grasslands - Kaisa A. Torppa; Carles Castaño; Anders Glimskär; Helle Skånes; Mårten Klinth; Tomas Roslin; Astrid R. Taylor; Maria Viketoft; Karina E. Clemmensen; Nadia I. Maaroufi (Agriculture, Ecosystems & Environment, 2024)

Exploring the benefits of intermediate crops: Is it possible to offset soil organic carbon losses caused by crop residue removal? - Sergio Alejandro Barrios Latorre; Helena Aronsson; Lovisa Björnsson; Maria Viketoft; Thomas Prade (Agricultural Systems, 2024)

Core taxa underpin soil microbial community turnover during secondary succession - Tord Ranheim Sveen; Maria Viketoft; Jan Bengtsson; Mohammad Bahram (Environmental Microbiology, 2024)
Understanding the processes that underpin the community assembly of bacteria is a key challenge in microbial ecology. We studied soil bacterial communities across a large‐scale successional gradient of managed and abandoned grasslands paired with mature forest sites to disentangle drivers of community turnover and assembly. Diversity partitioning and phylogenetic null‐modelling showed that bacterial communities in grasslands remain compositionally stable following abandonment and secondary succession but they differ markedly from fully afforested sites. Zeta diversity analyses revealed the persistence of core microbial taxa that both reflected and differed from whole‐scale community turnover patterns. Differences in soil pH and C:N were the main drivers of community turnover between paired grassland and forest sites and the variability of pH within successional stages was a key factor related to the relative dominance of deterministic assembly processes. Our results indicate that grassland microbiomes could be compositionally resilient to abandonment and secondary succession and that the major changes in microbial communities between grasslands and forests occur fairly late in the succession when trees have established as the dominant vegetation. We also show that core taxa may show contrasting responses to management and abandonment in grasslands.

Soil compaction effects on arbuscular mycorrhizal symbiosis in wheat depend on host plant variety - Kaisa A. Torppa; Johannes Forkman; Nadia I. Maaroufi; Astrid R. Taylor; Tanel Vahter; Martti Vasar; Martin Weih; Maarja Öpik; Maria Viketoft (Plant and Soil, 2023)
Background and aims Supporting arbuscular mycorrhizal (AM) nutrient acquisition in crops may reduce the need for fertilizer inputs, leading to more cost effective and sustainable crop production. In wheat, AM fungal responsiveness and benefits of symbiosis vary among varieties. This study explored the role of soil compaction in this variation. Methods We examined in a field experiment how soil compaction affects AM fungal colonization and biomass in five spring wheat varieties, and how these varieties differ in their AM-mediated phosphorus (P) uptake. We also studied soil properties, and AM fungal community composition in roots and soil. Results Soil compaction increased AM fungal colonization in the variety Alderon, characterized by root traits that indicate inefficient P uptake. Wheat P concentration and P:N ratio in Alderon and Diskett increased with increased root AM fungal colonization and biomass. In Diskett, which is the most cultivated spring wheat variety in Sweden and has intermediate root traits, total P content per m 2 also increased with root AM fungal colonization and biomass. Conclusions Some wheat varieties, potentially those characterized by P inefficient root traits, such as Alderon, may depend more on AM-mediated P uptake in compacted than in non-compacted soil. Increased P uptake with increased AM fungal colonization in Diskett suggests that efficient root and AM-mediated nutrient uptake can occur simultaneously in a modern variety. Breeding varieties that use roots and AM symbiosis as complementary strategies for nutrient uptake could improve nutrient uptake efficiency and help farmers achieve stable yields in varying conditions.

Political deafness may impede transition to biological control - Johan A. Stenberg; Paul G. Becher; Mattias Jonsson; Magnus Karlsson; Ingvar Sundh; Maria Viketoft (Trends in Plant Science, 2023)

Effects of copper contamination on N cycling microbial guilds and plant performance in two contrasting grassland soils - Ingrid Rijk; Linn Berkelund; Alf Ekblad; Sara Hallin; Dan B. Kleja; Astrid Taylor; Maria Viketoft; Christopher Jones (Soil Biology and Biochemistry, 2023)

Correction to: When is it biological control? A framework of definitions, mechanisms, and classifications - Johan A. Stenberg; Ingvar Sundh; Paul G. Becher; Christer Björkman; Mukesh Dubey; Paul A. Egan; Hanna Friberg; José F. Gil; Dan F. Jensen; Mattias Jonsson; Magnus Karlsson; Sammar Khalil; et al. (Journal of Pest Science, 2021)

When is it biological control? A framework of definitions, mechanisms, and classifications - Johan A. Stenberg; Ingvar Sundh; Paul G. Becher; Christer Björkman; Mukesh Dubey; Paul A. Egan; Hanna Friberg; José F. Gil; Dan F. Jensen; Mattias Jonsson; Magnus Karlsson; Sammar Khalil; et al. (Journal of Pest Science, 2021)
Biological control , or biocontrol , is the exploitation of living agents (incl. viruses) to combat pestilential organisms (incl. pathogens, pests, and weeds) for diverse purposes to provide human benefits. Thus, during the last century the practices and concepts involved have evolved in separate streams associated with distinct scientific and taxonomic disciplines. In parallel developments, there have been increasing references to biological control in industrial contexts and legislation, resulting in conceptual and terminological disintegration. The aim of this paper is to provide a global conceptual and terminological platform that facilitates future development of the field. We review use of previously suggested terms in key fields (e.g., phytopathology, entomology, and weed science), eliminate redundant terminology, identify three principles that should underpin the concept, and then present a new framework for biological control, rooted in seminal publications. The three principles establish that (1) only living agents can mediate biological control, (2) biological control always targets a pest, directly or indirectly, and (3) all biocontrol methods can be classified in four main categories depending on whether resident agents are utilized, with or without targeted human intervention ( conservation biological control and natural biological control , respectively) or agents are added for permanent or temporary establishment ( classical biological control and augmentative biological control , respectively). Correct identification of what is, and is not, biological control can help efforts to understand and optimize biological pest control for human and environmental benefits. The new conceptual framework may contribute to more uniform and appropriate regulatory approaches to biological control, and more efficient authorization and application of biocontrol products.

Additive effect of the root-lesion nematode Pratylenchus penetrans and the fungus Rhizoctonia solani on potato yield and damage - Maria Viketoft; Adam Flöhr; Jan-Eric Englund; Jonas Kardell; Eva Edin (Journal of Plant Diseases and Protection, 2020)
The significance of nematodes for disease development caused by other soil-borne pathogens has been demonstrated in many crops throughout the world and specifically prevalent are interactions between plant-parasitic nematodes and species of plant pathogenic fungi. Here, the interaction between the fungus Rhizoctonia solani (AG2) and the migratory endoparasitic root-lesion nematode Pratylenchus penetrans was investigated on potato. The hypotheses were that the combination of R. solani and P. penetrans would result in more severe canker lesions, reduced quality of the tubers and lower tuber yield, and we also expected higher nematode levels to render more nematode damage. To test this, potato plants were grown in pots in two replicate experiments and the presence and/or abundance of the two pathogens were controlled. The first three hypotheses were rejected as (1) the tuber yield decreased when the fungus and nematode occurred together but not more than the sum of their separate effects, i.e. additive, (2) there was no effect of presence of nematodes on the incidence of stem canker, and (3) the quality of tubers was actually partly improved as the presence of the nematodes reduced the likelihood of elephant hide on the tubers in one of the experiments. As expected, there were more visible nematode damages with addition of more nematodes, but beyond that the different nematode levels rendered in most cases similar responses. To have knowledge about interactions between pathogens, as the one showed here, is essential for disease control through appropriate management methods.

Cultivar Effects on the Interaction between Free-Living Plant-Parasitic Nematodes and the Fungal Pathogen Rhizoctonia solani in Potato - Maria Viketoft; Annhild Andersson; Eva Edin (American Journal of Potato Research, 2017)

Free-Living Plant-Parasitic Nematodes do not Affect the Efficiency of Seed Tuber Fungicide Treatment against Rhizoctonia solani - Eva Edin; Maria Viketoft (American Journal of Potato Research, 2017)

Above‐ and belowground insect herbivory modifies the response of a grassland plant community to nitrogen eutrophication - Pernilla Borgström; Joachim Strengbom; Lorenzo Marini; Maria Viketoft; Riccardo Bommarco (Ecology, 2017)
Understanding the role that species interactions play in determining the rate and direction of ecosystem change due to nitrogen (N) eutrophication is important for predicting the consequences of global change. Insects might play a major role in this context. They consume substantial amounts of plant biomass and can alter competitive interactions among plants, indirectly shaping plant community composition. Nitrogen eutrophication affects plant communities globally, but there is limited experimental evidence of how insect herbivory modifies plant community response to raised N levels. Even less is known about the roles of above‐ and belowground herbivory in shaping plant communities, and how the interaction between the two might modify a plant community's response to N eutrophication. We conducted a 3‐yr field experiment where grassland plant communities were subjected to above‐ and belowground insect herbivory with and without N addition, in a full‐factorial design. We found that herbivory modified plant community responses to N addition. Aboveground herbivory decreased aboveground plant community biomass by 21%, but only at elevated N. When combined, above‐ and belowground herbivory had a stronger negative effect on plant community biomass at ambient N (11% decrease) than at elevated N (4% decrease). In addition, herbivory shifted the functional composition of the plant community, and the magnitude of the shifts depended on the N level. The N and herbivory treatments synergistically conferred a competitive advantage to forbs, which benefited when both herbivory types were present at elevated N. Evenness among the plant species groups increased when aboveground herbivory was present, but N addition attenuated this increase. Our results demonstrate that a deeper understanding of how plant–herbivore interactions above and below ground shape the composition of a plant community is crucial for making reliable predictions about the ecological consequences of global change.

Long‐term effects of plant diversity and composition on soil nematode communities in model grasslands - Maria Viketoft; Janne Bengtsson; Björn Sohlenius; Matty P. Berg; Owen Petchey; Cecilia Palmborg; Kerstin Huss-Danell (Ecology, 2009)
An important component of plant–soil feedbacks is how plant species identity and diversity influence soil organism communities. We examine the effects of grassland plant species growing alone and together up to a richness of 12 species on nematode diversity and feeding group composition, eight years after the establishment of experimental grassland plots at the BIODEPTH site in northern Sweden. This is a substantially longer time than most other experimental studies of plant effects on soil fauna. We address the hypotheses that (1a) higher species or functional diversity of plants increases nematode diversity, as well as influences nematode community composition. Alternatively, (1b) individual plant species traits are most important for nematode diversity and community composition. (2) Plant effects on soil organisms will decrease with increasing number of trophic links between plants and soil fauna. Plant species identity was often more important than plant diversity for nematode community composition, supporting hypothesis 1b. There was a weak positive relation between plant and nematode richness, which could be attributed to the presence of the legume Trifolium pratense , but also to some other plant species, suggesting a selection or sampling effect. Several plant species in different functional groups affected nematode community composition. For example, we found that legumes increased bacterial‐feeding nematodes, most notably r ‐selected Rhabditida, while fungal‐feeding nematodes were enhanced by forbs. Other bacterial feeders and obligate root feeders were positively related to grasses. Plant effects were usually stronger on plant‐, bacterial‐ and fungal‐feeding nematodes than on omnivores/predators, which supports hypothesis 2. Our study suggests that plant identity has stronger effects than plant diversity on nematode community composition, but when comparing our results with similar previous studies the effects of particular plant species appear to vary. We also found that more productive plant species affected bacterial‐feeding nematodes more than fungal feeders. Moreover, we observed stronger effects the fewer the number of trophic links there were between a nematode feeding group and plants. Although we found clear effects of plants on soil nematodes, these were probably not large enough to result in strong and persistent plant–soil‐organism–plant feedback loops.